Changes in the chemical composition of V2O5-loaded CVC-TiO2 materials with calcination temperatures for NH3-SCR of NOx - Cha, Woojoon; Park, Eunseuk; Chin, Sungmin; Yun, Seong-Taek; Jurng, Jongsoo (SPRINGER, 2013)
In this study, the aim was to evaluate the effect of calcinations temperature on the catalytic activity and chemical composition of V2O5/TiO2. We prepared V2O5-loaded CVC-TiO2 catalysts by a combination of chemical vapor condensation (CVC) and impregnation method at different calcination temperatures. These catalysts were analyzed for their ability to catalyze NH3-based selective catalytic reduction of NOx. Compared with V2O5 loaded P25-TiO2 (commercial). V2O5/CVC-TiO2 catalysts calcined above 200 A degrees C exhibited better performance towards NOx conversion than that by a commercial catalyst prepared using P25-TiO2 (calcined at 500 A degrees C). In addition, the NOx conversion rate obtained with the sample calcined at 500 A degrees C gave the best result (90 %) at a reaction temperature of 200 A degrees C. From the XPS results, we observed that the V4+/5+ ratio was well balanced when the V2O5 loaded CVC-TiO2 sample was calcined at 500 A(0)C.
Keywords: SELECTIVE CATALYTIC-REDUCTION; OXIDE CATALYSTS; PHOTOCATALYTIC DEGRADATION; TIO2; PARTICLES; MECHANISM; OXIDATION; V2O5/TIO2; BEHAVIOR; TITANIA